Genomic vulnerability of a dominant seaweed points to future‐proofing pathways for Australia's underwater forests. (16th February 2021) - Wood, Georgina; Marzinelli, Ezequiel M.; Campbell, Alexandra H.; Steinberg, Peter D.; Vergés, Adriana; Coleman, Melinda A.
Abstract: Globally, critical habitats are in decline, threatening ecological, economic and social values and prompting calls for 'future proofing' efforts that enhance resilience to climate change. Such efforts rely on predicting how neutral and adaptive genomic patterns across a species' distribution will change under future climate scenarios, but data is scant for most species of conservation concern. Here, we use seascape genomics to characterise genetic diversity, structure and gene‐environmental associations in a dominant forest‐forming seaweed, Phyllospora comosa, along its entire latitudinal (12° latitude), and thermal (~14°C) range. Phyllospora showed high connectivity throughout its central range, with evidence of genetic structure and potential selection associated with sea surface temperatures (SSTs) at its rear and leading edges. Rear and leading‐edge populations harboured only half the genetic diversity of central populations. By modelling genetic turnover as a function of SST, we assessed the genomic vulnerability across Phyllospora's distributional range under climate change scenarios. Despite low diversity, range‐edge populations were predicted to harbour beneficial adaptations to marginal conditions and overall adaptability of the species may be compromised by their loss. Assisted gene flow from range edge populations may be required to enhance adaptation and increase resilience of central and leading‐edge populations under warming oceans. Understanding genomic vulnerability can inform proactive restoration and future‐proofing strategies for underwater forests and ensure their persistence in changing oceans. Abstract : Understanding genomic vulnerability can inform proactive restoration and future‐proofing strategies for underwater forests and ensure their persistence in changing oceans. Here, we developed a genomic toolbox to inform future‐proofing strategies for Phyllospora comosa, an endemic, forest‐forming seaweed inhabiting the south‐eastern Australian coastline that supports vital ecosystem functions, unique biodiversity and economic values.